Family, socioecomic and behaviour factors in oral health associated with dental caries severity in teenagers - Limaylla Cecilio, Rubén (2009)
The aim of this study was to determinate the prevalence and severity of caries, DMF-T y the relationship of family, socioeconomic and behavior in the oral health Factor level in a scholar adolescent; It surveyed, assessed a sample of 212 females between 12 and 17 years old with permanent teeth of the Institution Educative Secondary Nuestra Señora de las Mercedes in October 2008 in Huánuco, Perú. It found a caries prevalence of 85,8 %, a DMF-T of 4,0, the light severity of cavity was major (36,3 %); the age, number of persons per house, family caregiver, tooth brush frequency, intake of cariogenic products, dental care, types of dental care service. It concludes that the cavity prevalence was high; the DMF-T was moderate; severity and prevalence of caries increment with the rise of the age, increment of the number of person per house, the type and amount of caregivers, low tooth brush frequency, increment of intake of cariogenic products, the do not use dental care, the do not use of the types of dental care service.